Preparation, characterization, and antistatic applications of high‐density polyethylene/polyaniline blends - Ozkan, Ayse Nur; Sirin, Kamil (Polymers for advanced technologies, 2024)
To obtain electrostatic charge dissipative (ESD) materials, high‐density polyethylene (HDPE) and polyaniline (PANI) blends are synthesized by the solution blending method. To prepare the blends, 0.5, 1.0, and 3.0 wt% of PANI are introduced into the HDPE matrix. The prepared blends are investigated by Fourier transform infrared (FTIR) spectroscopy, X‐ray diffraction (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA), and scanning electron microscope (SEM). Additionally, stress–strain curves are used to examine the blends' mechanical properties. Polyaniline additions indicated an increase in thermal stability by approximately 1°C in the blends but decrease in mechanical properties. The four‐probe technique is used to determine the electrical conductivity of blends, which is found to be between 10−7 and 10−10 S/cm. The results of the conductivity values have indicated that all blends have great potential to be used as antistatic materials. For antistatic applications, the ESD performance of the blends is determined at different corona voltages. Blends achieved the antistatic requirements with a 10% cutoff decay time of approximately 2.0 s and a 1/e time of approximately 1.0 s, demonstrating quick dissipation of static charges. According to antistatic decay times, it has been shown that all blends obtained in this study can be used as antistatic material at 3 kV corona voltage.